2016
DOI: 10.1007/s11292-016-9267-x
|View full text |Cite
|
Sign up to set email alerts
|

The financial implications of merging proactive CCTV monitoring and directed police patrol: a cost–benefit analysis

Abstract: Objectives This study presents a cost-benefit analysis of an intervention pairing proactive CCTV monitoring with directed police patrol in Newark, NJ. A recent randomized control trial found that the strategy generated significant crime reductions in treatment areas relative to control areas. The current study focuses on the financial implications of the experimental strategy through a cost-benefit analysis. Methods The study begins by measuring the costs and benefits associated with the experimental strategy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
1
15
0
1
Order By: Relevance
“…However, examples of successful public systems are not completely absent. In addition, despite the financial commitments associated with CCTV, cost-benefit analyses suggest that achieved crime reductions can offset costs and even yield longer term monetary savings (La Vigne et al 2011), though CCTV may be more cost beneficial to society on a whole than the criminal justice system or any individual system component, including policing (Piza et al 2016). Farrington et al (2007) and Welsh and Farrington (2009a) found that CCTV worked best when integrated alongside other crime control strategies and when camera coverage was high.…”
Section: Discussionmentioning
confidence: 99%
“…However, examples of successful public systems are not completely absent. In addition, despite the financial commitments associated with CCTV, cost-benefit analyses suggest that achieved crime reductions can offset costs and even yield longer term monetary savings (La Vigne et al 2011), though CCTV may be more cost beneficial to society on a whole than the criminal justice system or any individual system component, including policing (Piza et al 2016). Farrington et al (2007) and Welsh and Farrington (2009a) found that CCTV worked best when integrated alongside other crime control strategies and when camera coverage was high.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the benefits of CCTV should exceed the cost of installation and maintenance for running the surveillance system. Piza, Gilchrist, Caplan, Kennedy and O'Hara (2016) argued that a proactive CCTV system can be cost effective for agencies with pre-existing CCTV infrastructure because they found the cost benefits in the Newark CCTV Directed Patrol strategy were more than $6.99 for every $1 invested.…”
Section: Effects Of Cctvsmentioning
confidence: 99%
“…Results from those studies show that CCTV's do reduce crime (Piza et al, 2019), but such crime reductions do not unambiguously justify their cost (Piza et al, 2016;Ratcliffe & Groff, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…10 By using both criminal justice and victim measures, we attempt to provide a complete account of crime costs by measuring both the impact of crime on municipal budgets (e.g., criminal justice costs) as well as the societal costs inflicted on residents of Denver generally. All crime costs were converted into 2015 (the median of our 3-year post period) dollars via the Bureau of Labor Statistics' Consumer Price Index Inflation calculator (McCollister, French, & Feng, 2010;Piza, Gilchrist, Caplan, Kennedy, & O'Hara, 2016). 11 To measure the monetary benefits provided by recreational marijuana dispensaries, we collected two categories of revenue: sales conducted by recreational dispensaries 12 and recreational marijuana taxes collected by the City of Denver.…”
Section: Monetary Costs and Benefitsmentioning
confidence: 99%